Thermal expansion and magnetic properties of benzoquinone-bridged dinuclear rare-earth complexes. Issue 39 (27th September 2017) - Moilanen, Jani O.; Mansikkamäki, Akseli; Lahtinen, Manu; Guo, Fu-Sheng; Kalenius, Elina; Layfield, Richard A.; Chibotaru, Liviu F.
Abstract : The complexes [BQ(MCl2 ·THF3 )2 ] (M = Y or Dy) possessing pentagonal bipyramidal environment around metal centers undergo significant thermal expansion as revealed by single-crystal X-ray and powder diffraction experiments. Abstract : The synthesis and structural characterization of two benzoquinone-bridged dinuclear rare-earth complexes [BQ(MCl2 ·THF3 )2 ] (BQ = 2, 5-bisoxide-1, 4-benzoquinone; M = Y (1 ), Dy (2 )) are described. Of these reported metal complexes, the dysprosium analogue2 is the first discrete bridged dinuclear lanthanide complex in which both metal centres reside in pentagonal bipyramidal environments. Interestingly, both complexes undergo significant thermal expansion upon heating from 120 K to 293 K as illustrated by single-crystal X-ray and powder diffraction experiments. AC magnetic susceptibility measurements reveal that2 does not show the slow relation of magnetization in zero dc field. The absent of single-molecule behaviour in2 arises from the rotation of the principal magnetic axis as compared to the pseudo- C 5 axis of the pentagonal bipyramidal environment as suggested by ab initio calculations. The cyclic voltammetry and chemical reduction experiments demonstrated that complexes1 and2 can be reduced to radical species containing [BQ 3 ˙ − ]. This study establishes efficient synthetic strategy to make bridged redox-active multinuclear lanthanide complexes with a pentagonal bipyramidal coordination environment that are potential precursors for single-molecule magnets.